Sustainable Apparel Product Purchase Decisions on Indonesian Gen Z and Millennial Women Consumers Using Theory of Planned Behaviour - Anggriani, Aulia; Daryanto, Arief; Asikin, Zenal (School of Business, IPB University (SB-IPB), 2024)
Sustainable and fast fashion brands compete to provide diverse choices for consumers. This study aims to identify characteristics of Indonesian Gen Z and millennial women consumers of sustainable apparel, analyze the influence of product attributes and marketing factors on their purchasing decisions, and examine the impact of individual and social factors using the theory of planned behavior. The target population is Instagram followers of the sustainable clothing official store who meet the criteria. The questionnaire was created using Google Forms and distributed through Instagram Direct Message. Seventy-seven willing respondents were obtained. Data analysis was carried out using the SEM-PLS method and descriptive analysis. Social norms, subjective norms, and individual behavior control factors significantly influence purchase intention and purchase decisions. However, sustainable clothing product attributes and marketing factors have a positive but insignificant impact on purchase intention and purchase decisions. Individual attitude factors weakly and insignificantly influence purchase intention and purchase decisions. Purchase intention, on the other hand, significantly influences purchase decisions. Five managerial implications are suggested: consumer segmentation, consumer-involved marketing strategies, collaboration with offline stores, enhancing sustainable product attributes, and improving the marketing of sustainable clothing products. Keywords: product attributes and marketing, purchase decision, SEM-PLS, sustainable apparel product, theory of planned behavior